Haitian, Bahamian, both or neither? Negotiations of ethnic identity among second-generation Haitians in the Bahamas. Issue 2 (4th March 2023) - Perry, Charmane M.
ABSTRACT: Using open-ended, semi-structured interviews, this essay analyzes the various ways second-generation Haitians negotiate their ethnic identity in the Bahamas. Second-generation Haitians are exposed to and sometimes forced to choose between two cultures because they have been told they cannot be both Haitian and Bahamian. Based on participant's responses, six categories emerged: individual, African/Black, Bahamian, Bahamian of Haitian descent, Haitian, and Haitian-Bahamian. This essay argues that second-generation Haitians negotiate similar sociocultural factors in the construction of their identity. Growing up in a country where there is a stigma of being Haitian, participants negotiated connection to culture, citizenship, stigma, belonging, and self-ascription/ascription by others. Further, I argue that identities such as Bahamian, Bahamian of Haitian descent, and Haitian-Bahamian are challenging ideas of what it means to be Bahamian. Last, I argue that the Haitian identity is formed primarily in resistance to and protection from the hostility experienced in the Bahamas.